Cone-beam X-ray tomography with arbitrary-orientation X-ray tube - Sueseenak, D.; Chanwimalueang, T.; Narkbuekaew, W.; Chitsakul, K.; Pintavirooj, C. (My University, 2006)
X-ray Computed Tomography is a technique to reconstruct an image of trans-axial slab of the object from a series of x-ray radiographs taken at a priorknown angle. Sequences of x-ray radiographs are served as two-dimensional projection data for a 3D tomography. The most popular Feldkamp Algorithm which is based on Filtered Backprojection (FBP) approaches has shown to perform well for 3D reconstruction. Conventional x-ray computed tomography was implemented on a c-arm x-ray apparatus where the x-ray tube and detector is capable of rotating to capture radiograph at any specific angle. In this paper, the concept of x-ray computed tomography for non c-arm x-ray apparatus was presented. In the purposed method, the cross-section of the object can be reconstructed from the multiple-viewed radiographs taken with arbitrary orientation of x-ray tube. The simulation results demonstrated the potential of such method. © 2006 IEEE.